Hubungan pola makan dengan kejadian hipertensi pada lansia di Kelurahan Bahu Lingkungan VI Kecamatan Malalayang Kota Manado - Margareth Sutjiato (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2022)
Background: Hypertension is a common disease in society. This condition in the long term can cause organ damage. Lifestyle in the community is one factor in the increase in cases of hypertension, one of which is diet.Purpose: This study aims to determine whether there is a relationship between diet and hypertension in the elderly in the village of Bahu Environment VI, Malalayang District, Manado City.Methods: This study is a quantitative study using a cross-sectional method with the independent variable (diet) and the dependent variable (hypertension). The population in this study was elderly in the Kelurahan Bahu environment VI, Malalayang District, Manado City, amounting to 84 people.Results: Results of this study obtained 22 (47,8%) respondents have poor dietary habits and there are 20 respondents (43,5%) with hypertension. The results of the chi-square test obtained a P value of 0.000 which means the P value is <0.05.Conclusion: There is a significant relationship between diet and the incidence of hypertension in the village of Bahu neighborhood VI, Malalayang district, Manado city. Half of the respondents have a bad diet.Keywords: Knowledge, Attitudes, Print media employees, COVID-19Â